Enhancing Capacity of Teachers of Foreign Languages in Public Higher Education Institutions through E-learning - Hang, Nguyen Thi Thuy (VNU Journal of Science: Policy and Management Studies; Vol 37 No 3, 2021)
The 4.0 industrial revolution in science and technology has brought about remarkable applications in higher education regarding e-learning which is described as a combination of information technology and education. Public higher institutions have been conducting e-learning across a wide variety of majors including foreign languages, which has created major reform in models and approaches towards foreign language teaching and learning. A new eco-learning system has been created to promote the digital capacity for teachers of foreign languages in public higher education institutions. Within the scope of this article, the author would like to focus on the impacts of e-learning on enhancing the capacity of teachers of foreign languages, then propose solutions to further exploit the advantages of e-learning in improving the capacity of teachers of foreign languages.